Roles and crosstalks of macrophages in diabetic nephropathy - Li, Hai-Di; You, Yong-Ke; Shao, Bao-Yi; Wu, Wei-Feng; Wang, Yi-Fan; Guo, Jian-Bo; Meng, Xiao-Ming; Chen, Haiyong (Frontiers in Immunology, 2022)
Diabetic nephropathy (DN) is the most common chronic kidney disease. Accumulation of glucose and metabolites activates resident macrophages in kidneys. Resident macrophages play diverse roles on diabetic kidney injuries by releasing cytokines/chemokines, recruiting peripheral monocytes/macrophages, enhancing renal cell injuries (podocytes, mesangial cells, endothelial cells and tubular epithelial cells), and macrophage-myofibroblast transition. The differentiation and cross-talks of macrophages ultimately result renal inflammation and fibrosis in DN. Emerging evidence shows that targeting macrophages by suppressing macrophages activation/transition, and macrophages-cells interaction may be a promising approach to attenuate DN. In the review, we summarized the diverse roles of macrophages and the cross-talks to other cells in DN, and highlighted the therapeutic potentials by targeting macrophages.